A survey of breastfeeding among women with previous surgery for benign breast disease: a descriptive exploratory study - Siying Mao; Jiafa He; Lezhen Huang; Yang Sun; Yan Dai; Qianqian Guo; Chang Qiu; Xue Song; Xiaojie Lin; Shengying Chen; Lingling Ye; Rui Xu (International Breastfeeding Journal, 2024)
Abstract Background Surgery is the primary treatment for benign breast disease and causes some disruption to the normal physiology of the breast, even when this disruption is localised, it remains unclear whether it affects women’s ability to breastfeed. There are only a few studies describing the experience of breastfeeding in women who have undergone benign breast disease (BBD) surgery. Methods We retrospectively analysed data from patients aged 20–40 years in Guangdong, China, who underwent breast lumpectomy for BBD in our department between 01 January 2013 and 30 June 2019, with a follow-up date of 01 February 2022. Patients were included who had a history of childbirth between the time of surgery and the follow-up date. By collecting general information about this group of patients and information about breastfeeding after surgery, we described the breastfeeding outcomes of women of a fertile age who had previously undergone surgery for benign breast disease. Results With a median follow-up of 5.9 years, a total of 333 patients met the inclusion criteria. From the breastfeeding data of the first child born postoperatively, the mean duration of ‘exclusive breastfeeding’ was 5.1 months, and the mean duration of ‘any breastfeeding’ was 8.8 months. The rate of ‘ever breastfeeding’ is 91.0%, which is lower than the national average of 93.7%, while the exclusive breastfeeding rate at six months was 40.8%, was higher than the 29.2% national average. The any breastfeeding rate at 12 months was 30.0%, which was well below the 66.5% national average. The common reason for early breastfeeding cessation was insufficient breast milk. A total of 29.0% of patients who had ever breastfed after surgery voluntarily reduced the frequency and duration of breastfeeding on the operated breast because of the surgery. Conclusions There are some impacts of BBD surgery on breastfeeding and some may be psychological. Institutions should provide more facilities for mothers who have undergone breast surgery to help them breastfeed, such as conducting community education on breastfeeding after breast surgery, training professional postoperative lactation consultants in hospitals, and extending maternity leave. Families should encourage mothers to breastfeed with both breasts instead of only the non-operated breast.